Pelatihan Keterampilan Dasar Strategi Pemasaran Pengolahan Hasil Laut Berbasis Blue Economy Bagi Masyarakat Nelayan : di Kabupaten Indramayu - Riyantie, Mayang; Rabbaniyah, Lathiefah; Utari, Eka Dewi; Suhendry, Bayu; Febriantina, Susan (Jurnal Pengabdian Kepada Masyarakat Kalam, 2025)
Karangsong Village in Indramayu Regency is one of the largest fish landing and marketing centers along the northern coast (Pantura) of West Java, with an average daily catch reaching 50 tons. However, this significant potential has not yet translated into substantial improvements in fishermen’s welfare, primarily due to limited marketing skills and a lack of understanding of sustainability concepts. This community service initiative aims to enhance the basic skills of marine product marketing strategies based on the Blue Economy for the fishing community in Karangsong Village. Through training and mentoring, the community is introduced to the importance of innovative seafood processing, value-added enhancement, and the application of marine ecosystem sustainability principles in fisheries business practices. The outcomes of the program indicate an increased understanding and skills among the fishermen regarding the Blue Economy concept and the urgency of maintaining sustainable fisheries practices across generations. This training is expected to serve as a starting point for building fishermen’s economic independence and strengthening coastal ecosystem resilience amidst the challenges of environmental changes and shifting market dynamics.